Innovative direction of complex use of waste of yeast production and bio-preparation "Radorod" in the leaf fall composting process - Pasenko, A.; Soloshych, I.; Dihtyar, S.; Ivasenko, Yu. (Scientific Progress & Innovations, 2024)
Modern approaches to the processing of waste of plant origin and organic waste of yeast production, which are valuable secondary raw materials for various branches of the economy, are analyzed. The paper proposes the complex use of waste from yeast production and biological preparation "Radorod" in the technology of composting vegetable waste. Biopreparation "Radorod" is a biodynamic fertilizer, which is produced by the method of aerobic mesophilic fermentation of organic raw materials, livestock waste with the addition of biological mass of plant origin. A positive effect of using a biological preparation containing actinomycetes in a complex with yeast cells of liquid waste in a ratio of 1 : 1 by mass was established. The synergistic effect of the complex bioagent contributes to the acceleration compared to the control of the process of aerobic oxidation of the organic component during composting of plant waste. There is an increase in the processes of mineralization of the plant substrate, an increase in the ash content of the product by 22.02–24.87 %. The simultaneous use of the biological preparation "Radorod" and yeast suspension as an analogue of liquid waste from yeast production in the technology of composting plant residues accelerates the process of aerobic oxidation of their organic component compared to the control, which is due to the biochemical activity of microorganisms-biodestroyers of the compost material, whose participation in mineralization processes is enhanced under the influence biologically active substances of Sacchagomyces cereuisiae and is replaced by introduction of Actinomyces species with biological preparation "Radorod". The resulting compost-fertilizer is sufficiently mineralized, enriched with nutrient compounds, and can be used in agriculture. The proposed eco-technological solution allows for the comprehensive disposal of waste from various branches of production, shortens the ripening time of compost, provides a natural stimulating effect on the bioagent of compost formation and obtains a quality product for further use in the agro-industrial complex.